2021
DOI: 10.31538/nzh.v4i2.1586
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Educational Management in The Context of Environmental Protection for Madrasah Application

Abstract: Environmental protection education in Indonesia must get the attention of all parties, especially the government and its staff, because healthy environmental resources must be pursued, not surrendered, let alone let them be damaged and extinct. For this reason, it takes the government's seriousness as the maker and implementer of policy regulations through education on environmental protection that is healthy and free from irresponsible human intervention. For this purpose, we have reviewed more than a hundred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
1
3
0
1
Order By: Relevance
“…Based on these scores, it can be concluded that H 0 is rejected, meaning that there is a significant influence on planning towards educational management in realizing madrasah educational governance. The results of the present study are in accordance with the results of the previous studies conducted by [3], [7]- [10], [12], [14]. Meanwhile, the difference between the results of the present study and the results of the previous studies are in the variable Z, that is: optimizing madrasah educational governance at which there is a significant influence in optimizing madrasah educational governance caused by the educational management and planning.…”
Section: Testing Sub Hypothesis 3 (Y Z)supporting
confidence: 90%
“…Based on these scores, it can be concluded that H 0 is rejected, meaning that there is a significant influence on planning towards educational management in realizing madrasah educational governance. The results of the present study are in accordance with the results of the previous studies conducted by [3], [7]- [10], [12], [14]. Meanwhile, the difference between the results of the present study and the results of the previous studies are in the variable Z, that is: optimizing madrasah educational governance at which there is a significant influence in optimizing madrasah educational governance caused by the educational management and planning.…”
Section: Testing Sub Hypothesis 3 (Y Z)supporting
confidence: 90%
“…The principal's responsibility in student activities is to coordinate, guide, and direct all student activities that have been designed and implemented. The principal in carrying out student management functions more as a person in charge of student activities, namely by guiding and directing planned student activities (Baharun et al, 2021;Raudah et al, 2021). The planning activities are student planning, new student admissions, student organization, student coaching, and service.…”
Section: Results and Discussion The Principal's Role As Supervisor At...mentioning
confidence: 99%
“…Raudah Raudah advised that environmental protection education in Indonesia must be considered by all parties, and it has been reviewed in more than 100 international publications. These publications discussed environmental security issues by applying them to school education in various contexts, thereby becoming a model for the application of religious schools in Indonesia [1]. Harring Niklas, through conducting research using the unique vertical dataset of seven Swedish universities and colleges, found that higher education in the social sciences would not produce stronger democratic or environmental norms, at least not in terms of environmental protection.…”
Section: Introductionmentioning
confidence: 99%